Ta'tsir Thoriqah al-Muthaabaqah fi Ta'lim al-Qawaid as-Sharfiyah ala Ihtimam Thalabah Ma'had al-Jami'ah - Utami, Alda Mila; Basyori, Ahmad (Jurnal Al-Mashadir: Journal of Arabic Education and Literature, 2024)
This research seeks to analyze how the 'Make a Match' technique influences students' levels of interest. The sample included 16 students from the fourth semester, chosen via purposive sampling. The tool for research was a questionnaire measuring learning interest, which was validated and tested for reliability, consisting of 20 items that reflect the indicators of learning interest. The results of the data analysis indicated that there was an increase in learning interest following the implementation of the 'Make a Match' approach. Hypothesis testing indicated a significance value below 0.001, demonstrating a substantial impact of the 'Make a Match' approach on students' interest, resulting in an 18% increase. Consequently, the 'Make a Match' approach proves to be very effective in boosting learning interest during morphology instruction.